Application of hyperbaric oxygen therapy in post-stroke patients - Dzięgielewski, Piotr; Mikołajewska, Emilia; Goch, Aleksander (Journal of Education, Health and Sport, 2015)
Dzięgielewski Piotr, Mikołajewska Emilia, Goch Aleksander. Hyperbaric oxygen therapy in post-stroke patients. Journal of Education, Health and Sport. 2015;5(8):302-306. ISSN 2391-8306. DOI 10.5281/zenodo.28813 http://dx.doi.org/10.5281/zenodo.28813 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A302-306 https://pbn.nauka.gov.pl/works/611442 POL-index https://pbn.nauka.gov.pl/polindex/browse/article/article-c640c258-b48f-4520-b83d-179a1f592c1b Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.07.2015. Revised 21.08.2015. Accepted: 21.08.2015. Hyperbaric oxygen therapy in post-stroke patients Piotr Dzięgielewski1, Emilia Mikołajewska1,2,3, Aleksander Goch1,4 1 Department of Physiotherapy, Ludwik Rydygier Collegium Medium in Bydgoszcz, Nicolaus Copernicus University in Toruń 2 Rehabilitation Clinic, The 10th Clinical Military Hospital with Policlinic, Bydgoszcz, Poland 3 Neurocognitive Laboratory, Interdisciplinary Center for Modern Technologies, Nicolaus Copernicus University in Toruń 4 Cardiology and Cardiosurgery Clinic, The 10th Clinical Military Hospital with Policlinic, Bydgoszcz, Poland Corresponding author: Emilia Mikołajewska Rehabilitation Clinic Military Clinical Hospital No. 10 and Polyclinic Powstańców Warszawy 5 85-681 Bydgoszcz, Poland e-mail: e.mikolajewska@wp.pl, emiliam@cm.umk.pl www: http://emikolajewska.netstrefa.eu Keywords: neurorehabilitation; physiotherapy; stroke; neurological deficit; brain edema; hyperbaric oxygen therapy; HBOT; neuroprotection; neurotherapeutic effect. Abstract Stroke is regarded as the major cause of brain damage, chronic neurological impairments, functional deficits, and long-term disability worldwide. Hyperbaric oxygen therapy (HBOT) might be taken into consideration as relatively novel method for brain repair. This article aims at analysis the extent to which the available ooprtunities are being exploited, including limitations associated with therapeutic use of HBOT in the therapy of post-stroke patients. Despite HBOT constitutes promising method in post-stroke patients further research is needed to better define the role of HBOT in the therapy of post-stroke patients.